An Interpersonal Meaning Analysis of Selected Episodes from Not Overthinking Podcast - Asrie Joestika Auliarachma; Budi Hermawan; Riesky Riesky (Passage, 2022)
In this pandemic era, some people seek knowledge and entertainment in digital audio content such as podcasts to reduce staring at computer and cell phone screens. Along with the massive trend, podcast speakers use particular language styles to get robust conversation and a large number of podcast listeners. Therefore, this study aims to identify the interpersonal meaning of the Not Overthinking podcast, as one of today's most popular podcasts. The data include the transcript texts of the three most popular episodes of the Not Overthinking podcast: “Why do we like to be correct?”, “Why are we scared to put ourselves out there?” and “Why do we struggle with consistency?” collected from Spotify. This study adopted Halliday and Matthiessen (2004) theory of Systemic Functional Linguistics (SFL), focusing on the mood types and speech functions. This study found all the mood types and speech functions in the data. The dominant mood type is declarative, and the dominant speech function is statement. The finding of this study provides a clearer picture of podcast speakers who use statements more often to share knowledge and experience. In addition, the speakers also positioned themselves equal to the listeners.